Characterization of the Temporomandibular Joint of Southern Sea Otters (Enhydra lutris nereis) - Lieske, Danielle; Vapniarsky, Natalia; Verstraete, Frank J. M.; Leale, Dustin M.; Young, Colleen; Arzi, Boaz (Frontiers in Veterinary Science, 2015)
The structure-function relationship of the temporomandibular joint (TMJ) of southern sea otter has largely not been described. This study aims to describe the histological, biochemical, and biomechanical features of the TMJ disc in the southern sea otter. The TMJ discs from fresh cadaver heads of southern sea otter adult males (n=8) and females (n=8) acquired from strandings were examined. Following macroscopical evaluation, the TMJs were investigated for their histological, mechanical and biochemical properties. We found that the sea otter TMJ discs are, in general, similar to other carnivores. Macroscopically, the TMJ disc was highly congruent and the mandibular head was encased tightly by the mandibular fossa with a thin disc separating the joint into two compartments. Histologically the articular surfaces were lined with dense fibrous connective tissue that gradually transitioned into one to two cell thick layer of hyaline-like cartilage. The disc fibres were aligned primarily in the rostrocaudal direction and had occasional lacuna with chondrocyte-like cells. The disc was composed primarily of collagen type 1. Biochemical analysis indicates sulphated glycosaminoglycan (sGAG) content lower than other mammals, but significantly higher in male sea otters than female sea otters. Finally, mechanical analysis demonstrated a disc that was stronger and stiffer in the rostrocaudal direction than the mediolateral direction, but also significantly stronger and stiffer in females than males. We conclude that the congruent design of the TMJ, thin disc, biochemical content, and mechanical properties all reflect a structure-function relationship within the TMJ disc that is likely designed for the sea otter’s hard diet and continuous food intake.